Addressing the Needs of Doctoral Students as Academic Practitioners: A Collaborative Inquiry on Teaching in Higher Education - Starr, Lisa J; DeMartini, Ashley (Canadian Journal of Higher Education, 2015)
This paper presents preliminary findings from a pilot study whose purpose was to explore how we, a tenure-track faculty member and a doctoral student, understood and developed our teaching practice when engaged in a formal faculty–student relationship. Using a hybrid of collaborative inquiry and collaborative self-study—which included verbal and written dialogue, interrogation, as well as observation—we sought to understand how that formal faculty–student relationship promoted the development of strong teaching pedagogy. The motivation for this study was a commitment to fostering high-quality teaching in undergraduate courses in our faculty of education. Driving this study was the research question: How are we investigating and improving upon our practices as teachers in post-secondary education?